Students’ awareness towards the Functions of Student Representative Council (SRC) in UiTM Seremban 3 during Open and Distance Learning (ODL) / Muhammad Iskandar Hamzah and Afiqah Nusrah Mohd Rouse - Hamzah, Muhammad Iskandar; Mohd Rouse, Afiqah Nusrah (2022)
The focus of this research is the students’ awareness towards the functions of Student Representative Council (SRC) during Open and Distance Learning (ODL) and the factor that may influence the students’ awareness which are the voting rights, the roles of the Student Representative Council (SRC) and the characteristics of the SRC members based on the Theory of Planned Behavior (TPB). This is because based on the literature review it was found that there is loss of interest participation among students towards anything that not related with the academic. Not only that, the changes of learning method to ODL have made anyone able to convey all problems or opinions directly to the authorities through various media and as for the representatives themselves explained that they were engage in campus politics because politic is the last thing on their mind due to they claim the council only a platform to meet new people, learn new skills and organize campus activities. This is why choosing unqualified representative will lead to the failure in term of function of the SRC and made students not aware functions of the SRC. Therefore, in order unravel, quantitative research design will be used where it examines the relevancy descriptive research as to describe the phenomena towards total population of 5,779 and sample size of is 357. As a result, the study indicates that roles of SRC are bound to be the most influencing effect on students’ awareness towards the functions of SRC which β = 0.393, p = 0.000 < 0.05 after the factors of the Theory of Planned Behavior (TPB) been lay down to the voting rights (attitudes), roles of the Students Representative Council (SRC) (subjective norms) and the characteristics of the Students Representative Council (SRC) members (perceived behavioral control).